Full waveform sonic seismic signature of high permeability sandstone: Perth Basin, Western Australia - AlMalki, Majed; Harris, Brett; Dupuis, J. Christian (CSIRO Publishing, 2010)
Often the most highly priced outcome from the application of geophysics methods in soft sediments is formation hydraulics and in particular the distribution of hydraulic permeability. Clear field examples of direct or even in-direct relationships between signals recorded by seismic methods and in-situ permeability in very high permeability sandstones are exceedingly rare. Therefore, relationships can only be investigated by making bothhigh precision acoustic measurements over a broad range of frequencies and making highly accurate measurements of in-situ permeability. We use multi-frequency Monopole Full Waveform Acoustic logging from the cored drill hole NG3. This drill hole intersected the Yarragadee formation in the Northern Gnangara Mound, Perth Basin; Western Australia. A key interval was selected and logged 4 times with transmitter centre frequencies including; 1, 3, 5 and 15 KHz. Under certain conditions P and Stoneley wave velocity dispersion can be connected to sandstone permeability.We infer velocity dispersion by considering the percent velocity differences for data collected over the same depth interval with distinct high and low dominant frequencies. It has been found that two sediment types showed some correlation between high velocity “dispersion“ and high measured core plug gas permeability. The two types are (a) interbedded gravelly sandstone and (b) cross-bedded sandstone. Cross plots for both sediment types show a general trend of increasing percent “dispersion” with increasing measured permeability. Values of 7-10% velocity difference between first arrival P wave data with transmitter dominant frequencies of 1 KHz and 15 KHz could be associated with the cross-bedded sandstones subset. Grouping and sorting sandstone layers based on sediment type as observed from core samples allows us to observe the positive correlation between high “dispersion” and high measured permeability in these weakly consolidated sandstones. This now leads to a requirement for more rigours and complete understanding of the physical meaning and mathematical expression of these relationships.